2017
DOI: 10.1515/aiht-2017-68-2998
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphisms of CYP2C9, CYP2C19, and CYP3A5 in Kosovar population

Abstract: Cytochrome P450 genetic polymorphisms are responsible for individual variations in drug metabolism and drug-drug interactions. They are very important for pharmacogenetics, and their frequency varies across different populations. There is a big gap in the knowledge about the CYP gene family polymorphisms in the population of Kosovo, and the aim of our study was to fill that gap by determining the frequency of the most important variant alleles of CYP2C9, CYP2C19, and CYP3A5 in 234 nonrelated Kosovars. The alle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…In the Serbian population the prevalence of the *2 allele was 16.3 % (p=0.97) and of the *17 allele 22.2 % (p=0.45). In the Croatian population it was 14.8 % (p=0.50) and 23.7 % (p=0.19), in the North Macedonian 14.4 % (p=0.48) and 20.1 % (p=0.93), and in the population of Kosovo 13.03 % (p=0.18) and 19.01 % (p=0.61), respectively ( 8 , 17 , 25 , 30 ). However, Russian and Greek studies showed a significant difference in the *2 allele prevalence (p=0.0002 and p=0.0035, respectively) ( 22 , 24 ).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…In the Serbian population the prevalence of the *2 allele was 16.3 % (p=0.97) and of the *17 allele 22.2 % (p=0.45). In the Croatian population it was 14.8 % (p=0.50) and 23.7 % (p=0.19), in the North Macedonian 14.4 % (p=0.48) and 20.1 % (p=0.93), and in the population of Kosovo 13.03 % (p=0.18) and 19.01 % (p=0.61), respectively ( 8 , 17 , 25 , 30 ). However, Russian and Greek studies showed a significant difference in the *2 allele prevalence (p=0.0002 and p=0.0035, respectively) ( 22 , 24 ).…”
Section: Resultsmentioning
confidence: 96%
“…However, one Romanian study ( 27 ) showed significantly higher prevalence of the *2 and *3 alleles (29 %, p<0.0001 and 20.2 %; p<0.0001, respectively). The general prevalences of the CYP2C9*2 and *3 alleles in the Caucasian population are about 13 % ( *2 ) and 7 % ( *3 ) ( 28 ) but significantly lower in the East Asians (0.01 % and 0.3 %), Africans (2 % and 1 %), and African-Americans (1 % and 0.5 %) ( 29 , 30 ). A more detailed comparison is available in Table 3 .…”
Section: Resultsmentioning
confidence: 98%
“…They are intended for the visualization of the complexity of ethnic categorization in pharmacogenetics literature and only reflect how these ethnic categories were classified in the literature we reviewed. A full list of ethnic categories included in this study can be found in Table S2 .
Figure 1Chart of ethnic categories which fall under the NIH term of “Asian”. Note: Data from references 7, 8, 10, 12, 14, 16, 28, 37, 41, 42, 48, 51, 7173, 8790.
Figure 2Chart of ethnic categories which fall under the NIH term of “Caucasian”. Note: Data from references 9, 11, 13, 18, 2026, 28, 34, 37, 4245, 70, 75, 87, 9194, 128.
Figure 3Chart of ethnic categories which fall under the NIH term of “Black”. Note: Data from references 11, 15, 16, 19, 2633, 3537, 40, 46, 47, 49, 50, 70, 75, 79, 87, 9497, 129, 130.
…”
Section: Methodsmentioning
confidence: 99%